PENERAPAN MODEL AUDITORY INTELLECTUALLY REPETITION DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN DATAR PADA SISWA KELAS V SD - Muyassaroh, Izzah (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Auditory Intellectually Repetition Model Using Concrete Objects in Improving Mathematics Learning about Geometry for the Fifth Grade Students of SDN 3 Selang in the Academic Year of 2015/2016. The objectives of this research is to improve Mathematics learning about geometry, This research is a collaborative Classroom Action Research (CAR) conducted in three cycle. Each cycle consisted of planning, action, observation, and reflection. Subjects of this research were 23 fifth grade students of SDN 3 Selang. The results of this research showed that the application of Auditory Intellectually Repetition (AIR) model using concrete objects that implemented with appropriate procedure can improve Mathematics learning about geometry for the fifth grade students of SDN 3 Selang in the academic year of 2015/2016. Keywords: Auditory Intellectually Repetition (AIR), concrete object, Mathematics Abstrak:Penerapan Model Auditory Intellectually Repetition dengan Media Konkret dalam Peningkatan Pembelajaran Matematika tentang Bangun Datar pada Siswa Kelas V SD Negeri 3 Selang Tahun Ajaran 2015/2016. Tujuan penelitian ini yaitu meningkatkan pembelajaran Matematika tentang bangun datar. Penelitian ini merupakan penelitian tindakan kelas (PTK) melalui tiga siklus, setiap siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN 3 Selang yang berjumlah 23 siswa. Hasil penelitian menunjukkan bahwa penerapan model AIR dengan media konkret yang dilaksanakan sesuai langkah yang tepat dapat meningkatkan pembelajaran Matematika tentang bangun datar pada siswa kelas V SDN 3 Selang tahun ajaran 2015/2016. Kata Kunci: Auditory Intellectually Repetition (AIR), media konkret, matematika